Functional, structural and phylogenetic analysis of domains underlying the Al sensitivity of the aluminum‐activated malate/anion transporter, TaALMT1. (5th November 2013) - Ligaba, Ayalew; Dreyer, Ingo; Margaryan, Armine; Schneider, David J.; Kochian, Leon; Piñeros, Miguel
Summary Triticum aestivum aluminum‐activated malate transporter (TaALMT1) is the founding member of a unique gene family of anion transporters (ALMTs) that mediate the efflux of organic acids. A small sub‐group of root‐localized ALMTs, including TaALMT1, is physiologically associated with in planta aluminum (Al) resistance. TaALMT1 exhibits significant enhancement of transport activity in response to extracellular Al. In this study, we integrated structure–function analyses of structurally altered TaALMT1 proteins expressed in Xenopus oocytes with phylogenic analyses of the ALMT family. Our aim is to re‐examine the role of protein domains in terms of their potential involvement in the Al‐dependent enhancement (i.e. Al‐responsiveness) of TaALMT1 transport activity, as well as the roles of all its 43 negatively charged amino acid residues. Our results indicate that the N‐domain, which is predicted to form the conductive pathway, mediates ion transport even in the absence of the C‐domain. However, segments in both domains are involved in Al3+ sensing. We identified two regions, one at the N‐terminus and a hydrophobic region at the C‐terminus, that jointly contribute to the Al‐response phenotype. Interestingly, the characteristic motif at the N‐terminus appears to be specific for Al‐responsive ALMTs. Our study highlights the need to include a comprehensive phylogenetic analysis when drawing inferences from structure–function analyses, as a significant proportion of the functional changes observed for TaALMT1 are most likely the result of alterations in the overall structural integrity of ALMT family proteins rather than modifications of specific sites involved in Al3+ sensing.